Solution of Linear and Quadratic Equations Based on Triangular Linear Diophantine Fuzzy Numbers - Naveed Khan; Naveed Yaqoob; Mudassir Shams; Yaé Ulrich Gaba; Muhammad Riaz (Journal of Function Spaces)
This paper is introducing a new concept of triangular linear Diophantine fuzzy numbers (TLDFNs) in a generic way. We first introduce the concept of TLDFNs and then study the arithmetic operations on these numbers. We find a method for the ranking of these TLDFNs. At the end, we formulate the linear and quadratic equations of the types A+X=B,A·X+B=C, and A·X2+B·X+C=D where the elements A,B,C, and D are TLDFNs. We provide a procedure for the solution of these equations using s,t,u,v-cut and also provide the examples.